Terrorism, Freshwater, and Environmental Pollution: Evidence of Afghanistan, Burkina Faso, Iraq, Arab Republic of Egypt, Cameroon, Mali, Mozambique, Niger, Nigeria, Somalia, Syrian Arab Republic, and Pakistan - Bildirici, Melike E.; Lousada, Sergio; Genc, Sema Yilmaz (MDPI, 2022)
Nowadays, the world is facing many important problems, including terrorism, drinkingwater supply problems, and environmental pollution, which have strong impacts on the sustainable development. In this paper, the cointegration between drinking water, terrorism, economic growth, energy consumption, and environmental pollution was explored in Afghanistan, Burkina Faso, Iraq, Arab Republic of Egypt, Cameroon, Mali, Mozambique, Niger, Nigeria, Somalia, Syrian Arab Republic, and Pakistan in the period of 2000-2020 by using the panel Fourier bootstrapping auto regressive distributed lag (PFBARDL) test, and then the direction of causality between the selected variables was determined. The PFBARDL test determined evidence of cointegration among the selected variables. The causality test found evidence of unidirectional causality from terrorism to drinking water and environmental pollution.
Keywords: causality; Fourier; drinking water; panel; panel Fourier bootstrapping ARDL; sustainability; terrorism; TRANSNATIONAL TERRORISM; ECONOMIC-GROWTH; RESOURCES; DISASTERS; CONFLICT; WARFARE; AGENTS; ROOTS; Environmental Sciences & Ecology; Water Resources